Pengaruh Periklanan dan Kualitas Produk terhadap Keputusan Membeli Handphone Merek Samsung PT. Telkomsel - Nurdin Nurdin; tjipto djuhartono (Sosio e-Kons, 2019)
This study aims to determine the effect of advertising media and product quality on the decision to buy mobile phones. Research Methods are survey research. The subject of this study as many as 50 people in the housing community di Perumahan Unggul Graha Permai. Data were collected by a questionnaire instrument using Likert. The validity of the data obtained by the validity and reliability test, all data have a normal distribution. The results showed that the advertising media gave a significant influence on the decision to buy a mobile phone. Likewise product quality gives a significant influence on the decision to buy a mobile phone. Coefficient of determination (R)2  is advertising media and product quality has a strong relationship to decision to buy handphone.